Surgical Treatment for Recurrent Refractory Skenitis - E. P. Miranda; D. C. Almeida; G. P. Ribeiro; J. M. Parente; A. G. Scafuri (The Scientific World Journal)
We report a case of persistent skenitis that was initially misdiagnosed and treated as a urinary infection. Despite an adequate course of antibiotics, the symptoms failed to improve. The case was ultimately resolved with surgical intervention, which resulted in its prompt and complete resolution.